Lithium ion conductor, lithium ion battery, and method for producing lithium ion conductor
By using the Ligax4 composite halide as a lithium ion in a lithium -ion battery, the problem of the electrolyte layer and electrode cracking are solved, and the stability and efficiency of the charging and discharge characteristics of the lithium ion battery are achieved.
Patent Information
- Application Number
- CN202380047331.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-04-27
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to completely suppress cracking of the electrolyte layer and electrode in lithium-ion batteries, resulting in a decrease in charge and discharge characteristics.
The composite halide is used as a lithium -ion -transmitted conductor represented by Ligax4. The composite halide has an increased nature of an ion conduction rate in a compressed state, and can perform sintering reactions at room temperature to repair the cracking of the electrode and electrolyte layer.
By containing the lithium ion transmission conductor in the electrode and electrolyte layer of the lithium ion battery, it can effectively repair the interface of cracking and prevent the interruption of the ion conduction pathway, thereby maintaining the stability of the charging characteristics.
Smart Images

Figure BDA0005189514120000271 
Figure BDA0005189514120000272 
Figure HDA0005189514130000011
Abstract
Description
Technical Field
[0001] The present application discloses a lithium ion conductor, a lithium ion battery, and a method for producing the lithium ion conductor. Background Art
[0002] In patent document 1, a negative electrode layer of an all-solid lithium ion battery is disclosed, which has particles of an alloy-based active material, and the particles of the alloy-based active material are twin crystal particles having two or more crystal orientations in one particle. In patent document 1, it is recorded that by using twin crystal particles as particles of an alloy-based active material, the stress generated inside the negative electrode layer is released to the twin crystal particles, and the cracking inside the negative electrode layer can be suppressed. In patent document 2, as a solid electrolyte constituting a solid electrolyte layer of an all-solid lithium ion battery, a solid electrolyte comprising a lithium salt, a sulfide solid electrolyte, and an organic electrolyte having a prescribed elastic modulus ratio is disclosed. The organic electrolyte disclosed in patent document 2 has the property that the ratio of the storage modulus to the loss modulus is reduced to less than 1 under heating. In patent document 2, by heating a solid electrolyte layer comprising a lithium salt, a sulfide solid electrolyte and an organic electrolyte, the organic electrolyte gradually shows the behavior as a liquid from the behavior as a solid as the temperature rises, and the organic electrolyte is adapted to the sulfide solid electrolyte, thereby improving the ion conductivity.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2020-092100
[0006] Patent Document 2: Japanese Patent Application Publication No. 2020-198270 Summary of the invention
[0007] Problems to be solved by the invention
[0008] Even if the crystal orientation in the active material particles is adjusted, it is difficult to completely suppress the cracking of the electrolyte layer and the electrode accompanying the charge and discharge of the lithium-ion battery. The cracking of the electrolyte layer and the electrode in the lithium-ion battery may reduce the charge and discharge characteristics of the lithium-ion battery. For lithium-ion batteries, a technology is needed that can suppress the reduction of the charge and discharge characteristics as much as possible when the electrolyte layer and the electrode crack occur.
[0009] Means for solving problems
[0010] The present application discloses the following multiple solutions as means for solving the above-mentioned problems.
[0011] <Option 1>
[0012] A lithium ion conductor comprising a complex halide represented by LiGaX4, wherein X is one or more halogens.
[0013] <Option 2>
[0014] The lithium ion conductor according to claim 1, wherein the complex halide contains a plurality of types of the halogen.
[0015] <Option 3>
[0016] The lithium ion conductor according to claim 1 or 2, wherein the complex halide contains at least one of Br and Cl.
[0017] <Option 4>
[0018] The lithium ion conductor according to any one of aspects 1 to 3, wherein the complex halide contains Br and I.
[0019] <Option 5>
[0020] A lithium ion battery comprising a positive electrode, an electrolyte layer, and a negative electrode, wherein at least one of the positive electrode, the electrolyte layer, and the negative electrode comprises the lithium ion conductor according to any one of aspects 1 to 4.
[0021] <Option 6>
[0022] The lithium ion battery according to embodiment 5, wherein at least one of the positive electrode, the electrolyte layer, and the negative electrode contains the lithium ion conductor and a sulfide solid electrolyte.
[0023] <Option 7>
[0024] A method for producing a lithium ion conductive material comprises: mixing at least one lithium halide and at least one gallium halide to obtain a complex halide represented by LiGaX4, wherein X is one or more halogens.
[0025] Effects of the Invention
[0026] The lithium ion conductor disclosed in the present invention is soft and has the property that the ion conductivity increases under pressure, and a reaction such as a sintering reaction can also occur at a low temperature around room temperature. By including such a lithium ion conductor in at least one of the electrode and the electrolyte layer of the lithium ion battery, when cracks occur in the electrode or the electrolyte layer, the cracked interface is repaired by the lithium ion conductor, and it is difficult for the lithium ion conduction path to be interrupted. That is, the lithium ion battery including the lithium ion conductor disclosed in the present invention can easily maintain the charge and discharge characteristics even when cracks occur in the electrolyte layer or the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1The structure of a lithium-ion battery is schematically shown.
[0028] Figure 2 The X-ray diffraction peaks of LiGaCl4 are shown.
[0029] Figure 3 The time dependence of the ionic conductivity of the particle battery in a pressurized state is shown. DETAILED DESCRIPTION
[0030] 1. Lithium ion conductor
[0031] The lithium ion conductor disclosed herein includes a complex halide represented by LiGaX4 (X is one or more halogens).
[0032] 1.1 Complex halides represented by LiGaX4
[0033] According to the new understanding of the inventors, the complex halide represented by LiGaX4 has the following properties: under pressure, the "room temperature sintering mechanism" in which the interface resistance disappears or decreases even at room temperature takes effect, and the ion conductivity gradually increases. On the other hand, when the lithium ion conductor is applied to various electrochemical devices, the lithium ion conductor can be in a state of being pressurized. Therefore, the lithium ion conductor disclosed in the present invention can easily exert high ion conductivity in various electrochemical devices. In addition, the complex halide is relatively soft, so it can follow the deformation of the surrounding materials. That is, the gaps caused by deformation, cracking, etc. of the material are filled by the lithium ion conductor disclosed in the present invention, and it is difficult to cause interruption of the ion conduction path.
[0034] Whether or not a complex halide represented by LiGaX4 is contained in a lithium ion conductor can be confirmed by X-ray diffraction or the like. That is, when an X-ray diffraction peak is obtained for the lithium ion conductor disclosed in the present invention using CuKα as a radiation source, the X-ray diffraction peak includes a diffraction peak from LiGaX4. Within the range confirmed by the inventors, the diffraction peak from LiGaX4 varies depending on the type of X, for example, the diffraction peak from LiGaCl4 appears at 15.3°±0.5°, 18.1°±0.5°, 18.7°±0.5°, 19.4°±0.5°, and 27.5°±0.5°.
[0035] In the complex halide represented by LiGaX4, X is one or more halogens, for example, at least one selected from Cl, Br and I. According to the new knowledge of the present inventors, when the complex halide has one or more of the following (1) to (3), the rate of increase in ion conductivity when maintained in a pressurized state tends to become particularly large, and it tends to become a more preferred substance as a lithium ion conductor.
[0036] (1) The above-mentioned complex halide contains a plurality of halogens.
[0037] (2) The above-mentioned complex halide contains at least one of Br and Cl.
[0038] (3) The above-mentioned complex halide contains Br and I.
[0039] According to the knowledge of the present inventors, when the composite halide contains Br as a halogen, by including at least one of Cl and I together with the Br, the increase rate of the ionic conductivity when maintained in a pressurized state is easily further increased. In this case, there is no particular restriction on the molar ratio of Cl, I and Br, and high ionic conductivity can be ensured at any molar ratio. In addition, when the composite halide contains Cl and I as halogens, if the molar ratio of Cl to the total of Cl and I is 50 mol% or more, the increase rate of the ionic conductivity when maintained in a pressurized state is particularly easy to increase.
[0040] In the lithium ion conductor disclosed in the present invention, the above-mentioned complex halide may have a crystal structure containing multiple LiGaX4, and may also have a eutectic structure containing multiple LiGaX4. That is, in the above-mentioned complex halide, multiple LiGaX4 are mutually dissolved, replaced, etc., and may become a substance having a structure and organization different from each individual structure and organization. The above-mentioned complex halide may have a eutectic structure of LiGaBr4 and LiGaCl4, a eutectic structure of LiGaBr4 and LiGaI4, a eutectic structure of LiGaCl4 and LiGaI4, and a eutectic structure of LiGaBr4, LiGaCl4, and LiGaI4. There is no particular limitation on the ratio of multiple LiGaX4. For example, in the case where the above-mentioned complex halide has a first complex halide represented by LiGaXa4 (wherein Xa is one of Br, Cl and I) and a second complex halide represented by LiGaXb4 (wherein Xb is a halogen different from Xa and is one of Br, Cl and I), the molar ratio of the first complex halide to the second complex halide (first complex halide / second complex halide) may be greater than 1 / 4 and less than 4, may be greater than 3 / 7 and less than 7 / 3, or may be greater than 2 / 3 and less than 3 / 2.
[0041] 1.2 Components other than complex halides represented by LiGaX4
[0042] The lithium ion conductor of the present disclosure may contain other halides in addition to the complex halide represented by LiGaX4. For example, it may contain LiX, GaX2, GaX3, LiGaX3, etc. That is, the lithium ion conductor of the present disclosure as its overall chemical composition does not necessarily contain Li, Ga, and X in a molar ratio of 1:1:4. In addition, it is believed that the complex halide constituting the lithium ion conductor of the present disclosure can also eutecticize other lithium compounds, and it is believed that the same effect is exerted in this case. For example, it is believed that by eutecticating at least one inorganic lithium compound selected from the following with the above-mentioned complex halide, the inorganic lithium compound can be softened or the lithium ion conductivity under pressure can be improved: B-based lithium salt; Al-based lithium salt; In-based lithium salt; other halogen-based lithium salts such as LiPF6 and LiBF4; hydride-based lithium salts such as LiBH4 and LiCBH; lithium sulfides such as Li3PS4 and LPSI; lithium oxides such as LLZO, LPO, and LLTO; other inorganic lithium compounds such as nitrates, hydroxides, sulfates, and carbonates, etc. Alternatively, organic lithium salts such as amide salts and imide salts such as LiTFSA (LiTFSI, lithium bistrifluoromethanesulfonyl imide), LiBETI (lithium bispentafluoroethanesulfonyl imide), LiFSA (LiFSI, lithium bisfluorosulfonyl imide), and LiFTA (LiFTI, lithium fluorosulfonyl (trifluoromethanesulfonyl) imide) can be combined with the above-mentioned complex halide.
[0043] As described above, the lithium ion conductor of the present disclosure may be composed of only the above-mentioned complex halide, or may be combined with other lithium compounds and the like.
[0044] In addition, the lithium ion conductor disclosed in the present invention may be a combination of the above-mentioned complex halide and a solid electrolyte. As for the solid electrolyte, for example, any solid electrolyte used as a solid electrolyte for a battery may be used. The solid electrolyte may be a sulfide solid electrolyte containing at least Li and S as constituent elements. In particular, the performance of a sulfide solid electrolyte containing at least Li, S and P as constituent elements is high, and the performance of a sulfide solid electrolyte containing at least one or more halogens based on a Li3PS4 skeleton is also high. As an example of a sulfide solid electrolyte, Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, Li I-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5-GeS2, etc. may be cited. The sulfide solid electrolyte may be amorphous or crystalline. The sulfide solid electrolyte may be in the form of particles, for example. The sulfide solid electrolyte may be used alone or in combination of two or more.
[0045] In the case where the lithium ion conductor of the present disclosure includes the above-mentioned composite halide and a sulfide solid electrolyte, the mass ratio of the sulfide solid electrolyte to the composite halide is not particularly limited. For example, when the total of the sulfide solid electrolyte and the composite halide is 100 mass%, the ratio of the sulfide solid electrolyte may be 40 mass% or more and less than 100 mass%, 50 mass% or more and less than 100 mass%, 60 mass% or more and less than 100 mass%, 70 mass% or more and less than 100 mass%, or 80 mass% or more and less than 100 mass%, and the ratio of the composite halide may be greater than 0 mass% and less than 60 mass%, greater than 0 mass% and less than 50 mass%, greater than 0 mass% and less than 40 mass%, greater than 0 mass% and less than 30 mass%, or greater than 0 mass% and less than 20 mass%.
[0046] When the lithium ion conductor of the present invention is used as an electrochemical device material, the above-mentioned complex halide, any solid electrolyte and other components can be combined. As other components, they can be appropriately determined according to the specific use of the lithium ion conductor. For example, when the lithium ion conductor is used as an electrode material for a lithium ion battery, an active material, a conductive aid and a binder can be combined with the lithium ion conductor. In addition, when the lithium ion conductor is used as a material for constituting an electrolyte layer of a lithium ion battery, a binder can be combined with the lithium ion conductor. The lithium ion conductor may contain the above-mentioned complex halide, any solid electrolyte, and other electrolytes (solid electrolytes other than sulfide solid electrolytes, liquid electrolytes). Furthermore, the lithium ion conductor of the present invention may contain various additives.
[0047] 2. Lithium-ion battery
[0048] The lithium ion conductor disclosed in the present invention can be used as a lithium ion conductive material in a lithium ion battery. Figure 1As shown, a lithium ion battery 100 according to one embodiment includes a positive electrode 10, an electrolyte layer 20, and a negative electrode 30. Among them, at least one of the positive electrode 10, the electrolyte layer 20, and the negative electrode 30 includes the lithium ion conductor of the present disclosure. As described above, the complex halide constituting the lithium ion conductor of the present disclosure is soft, and if the pressurized state is maintained, the ion conductivity gradually increases. Therefore, for example, during the manufacture of the battery, the complex halide deforms and fills the gaps between the electrodes and the electrolyte layer, so the filling rate in the electrodes and the electrolyte layer is easily increased. In addition, even if cracks, peeling, etc. occur in the electrodes and the electrolyte layer during the use of the battery, the complex halide is filled in the cracked part and the peeled part, so that the gaps caused by the cracks and peeling can be eliminated, and it is difficult for the ion conduction path to be interrupted. In addition, the lithium ion conductor of the present disclosure is easily in a pressurized state inside the lithium ion battery, and it is easy to exert excellent lithium ion conductivity. Furthermore, in lithium ion batteries using lithium metal, the lithium ion conductor disclosed in the present invention is used in combination, thereby also being expected to suppress the generation of dendrites. Thus, by including the lithium ion conductor disclosed in the present invention in at least one of the positive electrode 10, the electrolyte layer 20, and the negative electrode 30 of the lithium ion battery 100, the performance of the lithium ion battery 100 is easily improved.
[0049] In the lithium ion battery 100, a solid electrolyte, other liquid electrolytes or liquid additives may be used together with the lithium ion conductor of the present disclosure. The lithium ion battery 100 may be, for example, a fully solid battery that does not contain a liquid, or a battery that includes a solid electrolyte and a liquid. In particular, in the lithium ion battery 100, when at least one of the positive electrode 10, the electrolyte layer 20 and the negative electrode 30 includes the lithium ion conductor of the present disclosure and a solid electrolyte (particularly a sulfide solid electrolyte), the lithium ion conductor of the present disclosure can follow the deformation and cracking of the solid electrolyte, and even if a gap is generated due to the deformation and cracking of the sulfide solid electrolyte, the lithium ion conductor of the present disclosure fills the gap, thereby suppressing the interruption of the ion conduction path, etc.
[0050] 2.1 Positive Electrode
[0051] like Figure 1 As shown, the positive electrode 10 according to one embodiment may include a positive electrode active material layer 11 and a positive electrode current collector 12. In this case, the positive electrode active material layer 11 may include the above-mentioned lithium ion conductor.
[0052] 2.1.1 Positive electrode active material layer
[0053] The positive electrode active material layer 11 contains a positive electrode active material, and may further optionally contain an electrolyte, a conductive aid, a binder, etc. Furthermore, the positive electrode active material layer 11 may also contain various additives. In the case where the positive electrode active material layer 11 contains the lithium ion conductor of the present disclosure as an electrolyte, the positive electrode active material layer 11 contains a positive electrode active material in addition to the lithium ion conductor, and may further optionally contain other electrolytes, conductive aids, binders, and various additives. The respective contents of the positive electrode active material, electrolyte, conductive aid, and binder in the positive electrode active material layer 11 can be appropriately determined according to the target battery performance. For example, the entire positive electrode active material layer 11 (the entire solid component) is set to 100 mass%, and the content of the positive electrode active material can be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and can be less than 100 mass% or less than 90 mass%. There is no particular limitation on the shape of the positive electrode active material layer 11, for example, it can be a sheet with a roughly flat surface. The thickness of the positive electrode active material layer 11 is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, 10 μm or more, or 30 μm or less, or 2 mm or less, 1 mm or less, 500 μm or less, or 100 μm or less.
[0054] As the positive electrode active material, a known positive electrode active material as a positive electrode active material for a lithium ion battery can be used. Among the known active materials, a material that can show a potential (charge and discharge potential) of absorbing and releasing lithium ions higher than the potential of the negative electrode active material described later is used as a positive electrode active material. As the positive electrode active material, various composite oxides containing lithium such as lithium cobaltate, lithium nickelate, lithium manganate, lithium manganese nickel cobaltate, and spinel lithium compounds can be used. Oxide-based active materials other than composite oxides containing lithium can also be used, or sulfur-based active materials such as elemental sulfur and sulfur compounds can be used. The positive electrode active material can be used alone or in combination of two or more. The positive electrode active material can be, for example, in the form of particles, and its size is not particularly limited. The particles of the positive electrode active material can be solid particles, hollow particles, or particles with voids. The particles of the positive electrode active material can be primary particles, or secondary particles formed by the agglomeration of multiple primary particles. The average particle diameter (D50) of the particles of the positive electrode active material can be, for example, more than 1 nm, more than 5 nm, or more than 10 nm, and can be less than 500 μm, less than 100 μm, less than 50 μm, or less than 30 μm. It should be noted that the average particle diameter D50 mentioned in the present application is the particle diameter (median diameter) at the cumulative value 50% in the particle size distribution of the volume basis obtained by the laser diffraction-scattering method.
[0055] The surface of the positive electrode active material may be coated with a protective layer containing an ion conductive oxide. That is, the positive electrode active material layer 11 may include a composite having the above-mentioned positive electrode active material and a protective layer provided on its surface. As a result, it is easy to suppress the reaction between the positive electrode active material and the sulfide (such as the above-mentioned sulfide solid electrolyte, etc.). In the case where the battery is a lithium ion battery, examples of the ion conductive oxides that cover and protect the surface of the positive electrode active material include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, Li2WO4. The coverage (area ratio) of the protective layer can be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer can be, for example, 0.1nm or more or 1nm or more, or 100nm or less or 20nm or less.
[0056] The electrolyte that may be contained in the positive electrode active material layer 11 may be a solid electrolyte, a liquid electrolyte (electrolyte), or a combination thereof.
[0057] The solid electrolyte may be a solid electrolyte known as a solid electrolyte for lithium ion batteries. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, inorganic solid electrolytes are excellent in ion conductivity and heat resistance. In addition to the above-mentioned sulfide solid electrolytes, examples of inorganic solid electrolytes include lithium lanthanum zirconate, LiPON, Li 1+X Al X Ge 2-X (PO4)3, Li-SiO series glass, Li-Al-SO series glass and other oxide solid electrolytes. In particular, sulfide solid electrolytes, sulfide solid electrolytes containing at least Li, S and P as constituent elements, have high performance. In the case where the positive electrode active material layer 11 contains the lithium ion conductor of the present invention and also contains a solid electrolyte (especially a sulfide solid electrolyte), it can be expected that the lithium ion conductor of the present invention can be used to repair cracks in the solid electrolyte. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be, for example, in a particle form. One solid electrolyte may be used alone or two or more may be used in combination.
[0058] The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be, for example, a non-aqueous electrolyte. For example, as the electrolyte, a solution in which a lithium salt is dissolved at a predetermined concentration in a carbonate-based solvent may be used. As carbonate-based solvents, for example, fluoroethylene carbonate (FEC), ethylene carbonate (EC), dimethyl carbonate (DMC), etc. may be cited. As lithium salts, for example, hexafluorophosphates, etc. may be cited.
[0059] As the conductive aid that can be contained in the positive electrode active material layer 11, for example, carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), Ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel can be listed. The conductive aid can be, for example, in the form of particles or fibers, and there is no particular limitation on the size. The conductive aid can be used alone or in combination of two or more.
[0060] As the binder that can be contained in the positive electrode active material layer 11, for example, butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, polyacrylic acid-based binders, etc. can be listed. Only one type of binder can be used alone, or two or more types can be used in combination.
[0061] 2.1.2 Positive electrode collector
[0062] like Figure 1 As shown, the positive electrode 10 may include a positive electrode collector 12 in contact with the above-mentioned positive electrode active material layer 11. As for the positive electrode collector 12, any positive electrode collector generally used as a positive electrode collector of a battery can be used. In addition, the positive electrode collector 12 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, etc. The positive electrode collector 12 may be composed of a metal foil or a metal mesh. In particular, the metal foil has excellent handling properties. The positive electrode collector 12 may include a plurality of foils. As metals constituting the positive electrode collector 12, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. may be listed. In particular, from the viewpoint of ensuring oxidation resistance, etc., the positive electrode collector 12 may include Al. For the purpose of adjusting resistance, etc., the positive electrode collector 12 may have some coating on its surface. In addition, the positive electrode current collector 12 may be a material obtained by plating or vapor-depositing the above-mentioned metal on a metal foil or a substrate. In addition, when the positive electrode current collector 12 includes a plurality of metal foils, some layers may be provided between the plurality of metal foils. The thickness of the positive electrode current collector 12 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or less, and may be 1 mm or less or 100 μm or less.
[0063] In addition to the above-mentioned structure, the positive electrode 10 may include a general structure as a positive electrode of a lithium ion battery. For example, a pole piece, a terminal, etc. The positive electrode 10 can be manufactured by applying a known method. For example, by forming a positive electrode mixture containing the above-mentioned various components by a dry method or a wet method, the positive electrode active material layer 11 can be easily formed. The positive electrode active material layer 11 can be formed together with the positive electrode collector 12, or it can be formed separately from the positive electrode collector 12.
[0064] 2.2 Electrolyte layer
[0065] The electrolyte layer 20 contains at least an electrolyte. The electrolyte layer 20 may contain a solid electrolyte, and may further optionally contain a binder, etc. In the case where the electrolyte layer 20 contains the lithium ion conductor of the present disclosure as an electrolyte, the electrolyte layer 20 may further contain other electrolytes, binders and various additives in addition to the lithium ion conductor. In this case, there is no particular limitation on the content of the electrolyte and binder, etc. in the electrolyte layer 20. Alternatively, the electrolyte layer 20 may contain an electrolyte solution, and further, may have a separator, etc., for preventing the positive electrode active material layer 11 from contacting the negative electrode active material layer 31 while maintaining the electrolyte solution. There is no particular limitation on the thickness of the electrolyte layer 20, for example, it may be greater than 0.1 μm or greater than 1 μm, and may be less than 2 mm or less than 1 mm.
[0066] The electrolyte contained in the electrolyte layer 20 can be appropriately selected from the electrolytes exemplified as the lithium ion conductor of the present invention and the electrolytes that can be contained in the above-mentioned positive electrode active material layer. For example, when the electrolyte layer 20 contains the lithium ion conductor of the present invention and also contains a solid electrolyte (especially a sulfide solid electrolyte), the effect of repairing cracks of the solid electrolyte by the lithium ion conductor of the present invention can be expected. In addition, for the binder that can be contained in the electrolyte layer 20, it can be appropriately selected from the binders exemplified as the binders that can be contained in the above-mentioned positive electrode active material layer. Electrolytes and binders can each be used alone or in combination of two or more. In the case where the lithium ion battery is an electrolyte battery, the separator used to maintain the electrolyte can be any separator commonly used in lithium ion batteries, for example, separators containing resins such as polyethylene (PE), polypropylene (PP), polyester and polyamide can be listed. The separator can be a single-layer structure or a multi-layer structure. Examples of the multilayer separator include a 2-layer separator of PE / PP or a 3-layer separator of PP / PE / PP or PE / PP / PE. The separator may include a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric.
[0067] 2.3 Negative electrode
[0068] like Figure 1As shown, the negative electrode 30 according to one embodiment may include a negative electrode active material layer 31 and a negative electrode current collector 32 . In this case, the negative electrode active material layer 31 may include the above-mentioned lithium ion conductor.
[0069] 2.3.1 Negative electrode active material layer
[0070] The negative electrode active material layer 31 contains a negative electrode active material, and may further optionally contain an electrolyte, a conductive aid, a binder, etc. Furthermore, the negative electrode active material layer 31 may also contain various additives. In the case where the negative electrode active material layer 31 contains the lithium ion conductor of the present disclosure as an electrolyte, the negative electrode active material layer 31 contains a negative electrode active material in addition to the lithium ion conductor, and may further optionally contain other electrolytes, conductive aids, binders, and various additives. The respective contents of the negative electrode active material, electrolyte, conductive aid, and binder in the negative electrode active material layer 31 can be appropriately determined according to the target battery performance. For example, the entire negative electrode active material layer 31 (the entire solid content) is set to 100 mass%, and the content of the negative electrode active material can be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and can be less than 100 mass% or less than 90 mass%. There is no particular limitation on the shape of the negative electrode active material layer 31, for example, it can be a sheet with a roughly flat surface. The thickness of the negative electrode active material layer 31 is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, 10 μm or more, or 30 μm or less, or 2 mm or less, 1 mm or less, 500 μm or less, or 100 μm or less.
[0071] As the negative electrode active material, various materials whose potential for absorbing and releasing the specified ions (charge and discharge potential) is lower than that of the above-mentioned positive electrode active material can be used. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, etc. can be used. The negative electrode active material can be used alone or in combination of two or more. The shape of the negative electrode active material can be any shape that is generally used as a negative electrode active material for a lithium ion battery. For example, the negative electrode active material can be in the form of particles. The negative electrode active material particles can be primary particles or secondary particles formed by the aggregation of multiple primary particles. The average particle size (D50) of the negative electrode active material particles can be, for example, greater than 1 nm, greater than 5 nm, or greater than 10 nm, and can also be less than 500 μm, less than 100 μm, less than 50 μm, or less than 30 μm. Alternatively, the negative electrode active material can be in the form of a sheet (foil, film) such as lithium foil. That is, the negative electrode active material layer 31 may include a sheet of the negative electrode active material.
[0072] As electrolytes that may be contained in the negative electrode active material layer 31, the above-mentioned lithium ion conductor of the present invention, the above-mentioned solid electrolyte, an electrolyte solution or a combination thereof may be listed. For example, when the negative electrode active material layer 31 contains the lithium ion conductor of the present invention and also contains a solid electrolyte (particularly a sulfide solid electrolyte), it is possible to expect the effect of using the lithium ion conductor of the present invention to repair cracks in the solid electrolyte. As conductive aids that may be contained in the negative electrode active material layer 31, the above-mentioned carbon materials and the above-mentioned metal materials may be listed. The binder that may be contained in the negative electrode active material layer 31 may be appropriately selected, for example, from the binders exemplified as the binders that may be contained in the above-mentioned positive electrode active material layer 11. Each of the electrolyte and the binder may be used alone or in combination of two or more.
[0073] 2.3.2 Negative electrode collector
[0074] like Figure 1 As shown, the negative electrode 30 may include a negative electrode collector 32 in contact with the above-mentioned negative electrode active material layer 31. As for the negative electrode collector 32, any negative electrode collector generally used as a negative electrode collector of a battery can be used. In addition, the negative electrode collector 32 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, etc. The negative electrode collector 32 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, the metal foil has excellent handling properties. The negative electrode collector 32 may include a plurality of foils and sheets. As metals constituting the negative electrode collector 32, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. may be listed. In particular, from the viewpoint of ensuring reduction resistance and the viewpoint of being difficult to alloy with lithium, the negative electrode collector 32 may include at least one metal selected from Cu, Ni and stainless steel. For the purpose of adjusting resistance, etc., the negative electrode collector 32 may have some coating on its surface. In addition, the negative electrode current collector 32 may be a material obtained by plating or vapor-depositing the above-mentioned metal on a metal foil or a substrate. In addition, when the negative electrode current collector 32 includes a plurality of metal foils, some layers may be provided between the plurality of metal foils. The thickness of the negative electrode current collector 32 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or less, and may be 1 mm or less or 100 μm or less.
[0075] In addition to the above-mentioned structure, the negative electrode 30 may include a general structure as a negative electrode of a lithium ion battery. For example, it is a pole piece, a terminal, etc. The negative electrode 30 can be manufactured by applying a known method. For example, by forming the negative electrode mixture containing the above-mentioned various components by a dry method or a wet method, the negative electrode active material layer 31 can be easily formed. The negative electrode active material layer 31 can be formed together with the negative electrode collector 32, or it can be formed separately from the negative electrode collector 32.
[0076] 2.4 Other matters
[0077] The lithium-ion battery 100 can be a battery in which the above-mentioned structures are housed inside an outer casing. As for the outer casing, any outer casing known as an outer casing of a battery can be adopted. In addition, a plurality of lithium-ion batteries 100 can be electrically connected arbitrarily and overlapped arbitrarily to form a battery pack. In this case, the battery pack can be housed inside a known battery casing. The lithium-ion battery 100 can also include obvious structures such as necessary terminals. As the shape of the lithium-ion battery 100, for example, a coin type, a laminate type, a cylindrical type, and a square type can be listed.
[0078] The lithium ion battery 100 can be manufactured by applying a known method. For example, it can be manufactured as follows. However, the manufacturing method of the lithium ion battery 100 is not limited to the following method, and each layer can be formed by dry molding, for example.
[0079] (1) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used at this time is not particularly limited, and water or various organic solvents can be used. The positive electrode layer slurry is applied to the surface of the positive electrode collector using a scraper or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode collector to prepare a positive electrode.
[0080] (2) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used at this time is not particularly limited, and water or various organic solvents can be used. The negative electrode layer slurry is applied to the surface of the negative electrode collector using a scraper or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode collector to prepare a negative electrode.
[0081] (3) The layers are stacked in a manner such that the electrolyte layer (solid electrolyte layer or separator) is sandwiched between the negative electrode and the positive electrode to obtain a laminate having a negative electrode collector, a negative electrode active material layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode collector in this order. Other components such as terminals as required are attached to the laminate.
[0082] (4) The laminate is housed in a battery case. In the case of an electrolyte battery, the battery case is filled with an electrolyte, the laminate is immersed in the electrolyte, and the laminate is sealed in the battery case to prepare a lithium ion battery. It should be noted that in the case of a battery containing an electrolyte, the electrolyte can be contained in the negative electrode active material layer, the separator, and the positive electrode active material layer at the stage (3) above.
[0083] 3. Method for manufacturing lithium ion conductor
[0084] The lithium ion conductor of the present disclosure can be manufactured, for example, by mixing a lithium halide and a gallium halide. Specifically, the method for manufacturing the lithium ion conductor of the present disclosure may include: mixing at least one lithium halide and at least one gallium halide to obtain a complex halide represented by LiGaX4 (X is one or more halogens).
[0085] 3.1 Lithium halide
[0086] Examples of the lithium halide include lithium chloride, lithium bromide, lithium iodide, and combinations thereof. The lithium halide may be in any form as long as it can be mixed with the gallium halide, and may be in the form of particles, for example.
[0087] 3.2 Gallium Halide
[0088] Gallium halides include gallium chloride, gallium bromide, gallium iodide, or a combination thereof. Gallium halides may be in any form that can be mixed with lithium halides, for example, in the form of particles. The valence of gallium in the gallium halide may be divalent or trivalent, and in particular, it is easy to ensure high ion conductivity when it is trivalent. That is, as the gallium halide, GaX3 (X is one or more halogens) may be used.
[0089] 3.3 Mixing ratio
[0090] As for the mixing ratio of lithium halide and gallium halide, it is sufficient as long as it is a ratio that generates LiGaX4 in the lithium ion conductor after mixing. For example, the molar ratio (Li / Ga) of lithium in lithium halide to gallium in gallium halide can be greater than 0.6 and less than 1.5. The molar ratio can be greater than 0.7, greater than 0.8, or greater than 0.9, and can be less than 1.4, less than 1.3, less than 1.2, or less than 1.1.
[0091] 3.4 Hybrid approach
[0092] The composite halide constituting the lithium ion conductor of the present disclosure can be produced, for example, by mixing the lithium halide and the gallium halide while applying stress. The stress may be, for example, friction, shear force, shear stress, impact force, etc. As a method of applying such stress during mixing, for example, a method of mixing while pulverizing using a mechanical mixing means such as a ball mill can be cited.
[0093] 4. How to use lithium ion conductors
[0094] The technology disclosed in the present invention also has an aspect of a method for using a lithium ion conductor. That is, the method for using the lithium ion conductor disclosed in the present invention is characterized in that, in an electrochemical device, the lithium ion conductor disclosed in the present invention is used while being pressurized. For example, the lithium ion conductor disclosed in the present invention is used in a pressurized state in at least one of the positive electrode, electrolyte layer, and negative electrode of a lithium ion battery. There is no particular limitation on the magnitude of the pressure applied to the lithium ion conductor. For example, in the case where a lithium ion conductor is contained in a pressurized state in at least one of the positive electrode, electrolyte layer, and negative electrode of a lithium ion battery, the pressure applied to the lithium ion conductor may be greater than 0.1 MPa and less than 100 MPa, greater than 1 MPa and less than 50 MPa, or greater than 5 MPa or less than 30 MPa.
[0095] 5. Method for charging and discharging a lithium-ion battery and method for improving the cycle characteristics of a lithium-ion battery
[0096] In the case where the lithium ion conductor of the present invention is contained in at least one of the positive electrode, electrolyte layer and negative electrode of a lithium ion battery, the charge and discharge cycle characteristics of the lithium ion battery can be easily improved. That is, the charge and discharge method of the lithium ion battery and the method for improving the cycle characteristics of the lithium ion battery of the present invention are characterized in that the lithium ion battery is repeatedly charged and discharged, the lithium ion battery has a positive electrode, an electrolyte layer and a negative electrode, at least one of the positive electrode, the electrolyte layer and the negative electrode contains the lithium ion conductor of the present invention, and when a gap is generated in at least one of the positive electrode, the electrolyte layer and the negative electrode as the lithium ion battery is charged and discharged, at least a part of the gap is eliminated by using the lithium ion conductor of the present invention. Here, the so-called "gap" can be generated in at least one of the positive electrode, the electrolyte layer and the negative electrode as the volume of the active material changes. "Gap" is a concept including "crack" and the like. It is believed that by eliminating at least a part of the gap using the ion conductor of the present invention (that is, filling at least a part of the gap with the lithium ion conductor of the present invention), the ion conduction path and the conductive path interrupted by the gap can be restored.
[0097] 6. Vehicles with lithium-ion batteries
[0098] As described above, when the lithium ion conductor of the present invention is included in at least one of the positive electrode, electrolyte layer and negative electrode of the lithium ion battery, it is possible to expect an improvement in the charge and discharge cycle characteristics of the lithium ion battery. Such a lithium ion battery with excellent charge and discharge cycle characteristics can be suitable for use in at least one vehicle selected from a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV) and an electric vehicle (BEV). That is, the technology of the present disclosure also has an aspect as a vehicle, which is a vehicle having a lithium ion battery, the lithium ion battery having a positive electrode, an electrolyte layer and a negative electrode, and at least one of the positive electrode, the electrolyte layer and the negative electrode contains the lithium ion conductor of the present disclosure.
[0099] Example
[0100] As described above, one embodiment of the lithium ion conductor, lithium ion battery, and method for manufacturing a lithium ion conductor of the present disclosure has been described, but the lithium ion conductor, lithium ion battery, and method for manufacturing a lithium ion conductor of the present disclosure can be modified in various ways other than the above-described embodiment without departing from the gist thereof. The following examples are shown to explain the technology of the present disclosure in more detail, but the technology of the present disclosure is not limited to the following examples.
[0101] 1. Synthesis of complex halides as lithium ion conductors
[0102] 1.1 Example 1
[0103] LiCl (manufactured by Kojun Chemical Co., Ltd.) and GaCl3 (manufactured by Tokyo Chemical Industry Co., Ltd.) were weighed in a molar ratio of 50:50, put into a 500 ml ZrO2 tank, put into a φ5 mm ZrO2 ball, put into a state where 100 g of heptane (manufactured by Kanto Chemical Co., Ltd.), and pulverized at a speed of 300 rpm for 1 hour, and this was repeated 20 times. The mixture was dried to obtain LiGaCl4.
[0104] 1.2 Example 2
[0105] LiGaI4 was obtained by mixing in the same manner as in Example 1 except that LiI (manufactured by Gaochun Chemical Co., Ltd.) was used instead of LiCl and GaI3 (manufactured by Aldrich Co., Ltd.) was used instead of GaCl3. LiGaCl4 and LiGaI4 synthesized in the same manner as in Example 1 were mixed in a molar ratio of 80:20, and heated and stirred at a temperature above the melting point to obtain a melt. The obtained melt was cooled to room temperature and pulverized in a mortar to obtain 80LiGaCl4-20LiGaI4 as a molten salt.
[0106] 1.3 Example 3
[0107] 50LiGaCl4-50LiGaI4 as a molten salt was obtained by the same procedure as in Example 2 except that LiGaCl4 and LiGaI4 were mixed in a molar ratio of 50:50.
[0108] 1.4 Example 4
[0109] LiGaBr4 was synthesized by mixing in the same manner as in Example 1 except that LiBr (manufactured by Kojun Chemical Co., Ltd.) was used instead of LiCl and GaBr3 (manufactured by Alpha Corporation) was used instead of GaCl3. LiGaCl4 and LiGaBr4 synthesized in the same manner as in Example 1 were mixed in a molar ratio of 80:20, and heated and stirred at a temperature above the melting point to obtain a melt. The obtained melt was cooled to room temperature and pulverized in a mortar to obtain 80LiGaCl4-20LiGaBr4 as a molten salt.
[0110] 1.5 Example 5
[0111] 50LiGaCl4-50LiGaBr4 as a molten salt was obtained by the same procedure as in Example 4 except that LiGaCl4 and LiGaBr4 were mixed in a molar ratio of 50:50.
[0112] 1.6 Example 6
[0113] 20LiGaCl4-80LiGaBr4 as a molten salt was obtained by the same procedure as in Example 4 except that LiGaCl4 and LiGaBr4 were mixed in a molar ratio of 20:80.
[0114] 1.7 Example 7
[0115] LiGaBr4 was obtained by mixing in the same manner as in Example 1 except that LiBr (manufactured by Kojun Chemical Co., Ltd.) was used instead of LiCl and GaBr3 (manufactured by Alpha Corporation) was used instead of GaCl3.
[0116] 1.8 Example 8
[0117] LiGaBr4 and LiGaI4 were mixed in a molar ratio of 80:20, and heated and stirred at a temperature above the melting point to obtain a melt. The obtained melt was cooled to room temperature and then pulverized in a mortar to obtain 80LiGaBr4-20LiGaI4 as a molten salt.
[0118] 1.9 Example 9
[0119] LiGaBr4 and LiGaI4 were mixed in a molar ratio of 70:30, and heated and stirred at a temperature above the melting point to obtain a melt. The obtained melt was cooled to room temperature and then pulverized in a mortar to obtain 70LiGaBr4-30LiGaI4 as a molten salt.
[0120] 1.10 Example 10
[0121] LiGaBr4 and LiGaI4 were mixed in a molar ratio of 60:40, and heated and stirred at a temperature above the melting point to obtain a melt. The obtained melt was cooled to room temperature and then pulverized in a mortar to obtain 60LiGaBr4-40LiGaI4 as a molten salt.
[0122] 1.11 Example 11
[0123] LiGaBr4 and LiGaI4 were mixed in a molar ratio of 50:50, and heated and stirred at a temperature above the melting point to obtain a melt. The obtained melt was cooled to room temperature and then pulverized in a mortar to obtain 50LiGaBr4-50LiGaI4 as a molten salt.
[0124] 1.12 Example 12
[0125] LiGaBr4 and LiGaI4 were mixed in a molar ratio of 40:60, and heated and stirred at a temperature above the melting point to obtain a melt. The obtained melt was cooled to room temperature and then pulverized in a mortar to obtain 40LiGaBr4-60LiGaI4 as a molten salt.
[0126] 1.13 Example 13
[0127] LiGaBr4 and LiGaI4 were mixed in a molar ratio of 40:60, and heated and stirred at a temperature above the melting point to obtain a melt. The obtained melt was cooled to room temperature and then pulverized in a mortar to obtain 20LiGaBr4-80LiGaI4 as a molten salt.
[0128] 1.14 Comparative Example 1
[0129] LiCl and AlCl3 (manufactured by Wako Pure Chemical Industries, Ltd.) were weighed in a molar ratio of 50:50, put into a 500 ml ZrO2 tank, put into a φ5 mm ZrO2 ball, put into a 100 g heptane (manufactured by Kanto Chemical Co., Ltd.), and pulverized at a speed of 300 rpm for 1 hour, and repeated 20 times. The mixture was dried to obtain LiAlCl4.
[0130] 1.15 Comparative Example 2
[0131] A Li-PSI-Br based sulfide solid electrolyte is prepared.
[0132] 2. Confirmation of Crystal Structure
[0133] exist Figure 2 The X-ray diffraction peaks of LiGaCl4 in Example 1 are shown in FIG. Figure 2 It can be seen that in the X-ray diffraction peaks of LiGaCl4 obtained after mixing using a ball mill, the peaks from LiCl and GaCl3 as raw materials are basically not confirmed (or, the peaks are reduced compared to the raw materials), and a crystal phase different from LiCl and GaCl3 is generated. Specifically, it can be seen that a crystal phase related to LiGaCl4 is generated. Similarly, for Example 7, a crystal phase related to LiGaBr4 is confirmed. In addition, for Examples 2 to 6 and Examples 8 to 13, eutectic structures with each complex halide are confirmed.
[0134] 3. Determination of ionic conductivity
[0135] The ion conductivity of each lithium ion conductor of Examples 1 to 13 and Comparative Examples 1 and 2 was measured. Specifically, 150 mg of the ion conductor was filled into a cylinder and uniaxially pressed to produce a particle battery. The particle was placed in a desiccator and the impedance was measured at 25°C using a thermostatic bath. The ion conductivity after pressing was calculated from the obtained resistance value and the sample thickness. The particle battery was placed in a thermostatic bath for a certain period of time, the resistance value at the moment when the resistance was reduced to saturation was read, and the ion conductivity after storage was calculated.
[0136] 4. Preparation and evaluation of evaluation batteries
[0137] 4.1 Application Example 1
[0138] 4.1.1 Preparation of negative electrode composites
[0139] The sulfide solid electrolyte of Comparative Example 2 and the molten salt of Example 2 were weighed to a volume ratio of 80:20 to obtain a mixed electrolyte. Crystalline Si as a negative electrode active material, the mixed electrolyte, and VGCF as a conductive additive were mixed in a mortar to obtain a negative electrode composite.
[0140] 4.1.2 Preparation of positive electrode composite materials
[0141] As the positive electrode active material, NCM (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), the sulfide solid electrolyte of Comparative Example 2, and VGCF as a conductive aid were mixed in a mortar to obtain a positive electrode composite.
[0142] 4.1.3 Battery Production
[0143] In an alumina cylinder of φ11.28 mm, the positive electrode composite, the sulfide solid electrolyte of Comparative Example 2, and the negative electrode composite were laminated and pressed at 6 t to obtain a laminate consisting of a positive electrode composite layer / sulfide solid electrolyte layer / negative electrode composite layer. The laminate was restrained at 6 N to produce an all-solid-state battery for evaluation.
[0144] 4.1.4 Charge and discharge cycle test
[0145] The fabricated all-solid-state battery was subjected to 50 cycles of CCCV charge and discharge at a charge and discharge rate of 1 / 3C at room temperature, and the ratio of the capacity after 50 cycles to the initial capacity was calculated as the “capacity retention rate”.
[0146] 4.2 Application Comparative Example 1
[0147] A full solid-state battery was prepared in the same manner as in Example 1, except that LiAlCl 4 of Comparative Example 1 was used in the negative electrode composite instead of the molten salt of Example 2, and a charge and discharge cycle test was performed.
[0148] 4.3 Application Comparative Example 2
[0149] A full solid-state battery was prepared in the same manner as in Application Example 1, except that only the sulfide solid electrolyte of Comparative Example 2 was used as the electrolyte in the negative electrode composite, and a charge and discharge cycle test was performed.
[0150] 5. Evaluation results
[0151] Table 1 below shows the types and ion conductivities of the lithium ion conductors of Examples 1 to 13 and Comparative Examples 1 and 2. Table 2 below shows the results of measuring the capacity retention rates of all-solid batteries using Example 1 and Comparative Examples 1 and 2. Figure 3 Graph 2 shows the time dependence of the ion conductivity of the particle battery of Example 2.
[0152] [Table 1]
[0153] (Table 1)
[0154]
[0155] [Table 2]
[0156] (Table 2)
[0157]
[0158] From Tables 1 and 2 and Figure 3 The results shown show the following.
[0159] As shown in Table 1, it can be seen that the ion conductivity of the lithium ion conductors of Examples 1 to 13 gradually increases even at room temperature (25°C) while maintaining the pressurized state. That is, it is believed that the "room temperature sintering mechanism" of the lithium ion conductors of Examples 1 to 13, in which the interface resistance disappears or decreases at room temperature, operates under the pressurized state. Specifically, the lithium ion conductors involved in Examples 1 to 13 undergo room temperature sintering when pressurized to form particle batteries, and the interface resistance gradually disappears, and the ion conductivity increases. Figure 3 As shown, it can be seen that when the particle battery is crushed and pressurized again to form a particle battery, the interface resistance disappears and the ion conductivity increases, just like before crushing. That is, it can be seen that the lithium ion conductors of Examples 1 to 13 can repeatedly undergo room temperature sintering and the disappearance of interface resistance due to pressurization. In addition, the lithium ion conductors involved in Examples 1 to 13 are relatively soft and can follow the deformation of the surrounding materials. It is believed that when such a lithium ion conductor is applied to a lithium ion battery, even if the active material expands and contracts during charging and discharging, cracks occur in the solid electrolyte, etc., the lithium ion conductor can be used to repeatedly repair the cracked interface. As a result, as shown in Table 2, the cycle characteristics of the battery are improved, and a high capacity can be maintained before and after the charge and discharge cycle. As for such an effect, it was not confirmed in Comparative Examples 1 and 2, and it can be seen that this is a unique effect produced by the composite halide of Li and Ga.
[0160] It should be noted that in the above-mentioned Examples 1 to 13, the case where a lithium ion conductor containing a complex halide represented by LiGaX4 (X is one or more halogens) is applied to the negative electrode of a lithium ion battery is exemplified, but it is believed that the lithium ion conductor can exert the desired effect whether it is contained in any of the positive electrode, the electrolyte layer and the negative electrode. In particular, by containing it in the negative electrode, a higher effect can be expected. For example, when an alloy-based active material (Si, Si alloy, Sn, Sn alloy, etc., especially Si) is used as the negative electrode active material, the expansion and contraction of the negative electrode active material during charging and discharging is large, and cracking and peeling are likely to occur in the negative electrode with charging and discharging. As a result, by containing the above-mentioned lithium ion conductor, the crack interface is repaired by the lithium ion conductor, and it is easy to significantly suppress the interruption of the ion conduction path.
[0161] In addition, in the above-mentioned Examples 1 to 13, the case where a lithium ion conductor containing a complex halide represented by LiGaX4 (X is one or more halogens) is applied to an all-solid lithium ion battery that does not contain substantially any liquid is exemplified, but the lithium ion conductor can also be applied to a lithium ion battery containing a liquid. Among them, when the lithium ion conductor is used together with a solid electrolyte, it is easy to play the effect of repairing cracks and peeling of the solid electrolyte. That is, when the lithium ion conductor is applied to a battery containing a solid electrolyte, a higher effect can be expected.
[0162] According to the above results, it can be said that the lithium ion conductor containing the complex halide represented by LiGaX4 (X is one or more halogens) is soft and has the property of increasing ion conductivity under pressure, and a reaction such as sintering reaction can also occur at a low temperature around room temperature. By containing such a lithium ion conductor in at least one of the electrode and the electrolyte layer of the lithium ion battery, even if cracks occur in the electrode or the electrolyte layer, the cracked interface can be repaired by the lithium ion conductor, and the interruption of the lithium ion conduction path can be suppressed. That is, the lithium ion battery containing this lithium ion conductor is easy to maintain the charge and discharge characteristics even if cracks occur in the electrolyte layer and the electrode.
[0163] Description of Reference Numerals
[0164] 10 Positive electrode
[0165] 11 Positive electrode active material layer
[0166] 12. Positive electrode collector
[0167] 20 Electrolyte layer
[0168] 30 Negative electrode
[0169] 31 Negative electrode active material layer
[0170] 32 Negative electrode collector
[0171] 100 Lithium-ion battery
Claims
1. A lithium ion conductor comprising a complex halide represented by LiGaX4, wherein: X is one or more halogens.
2. The lithium ion conductor according to claim 1, wherein The complex halide contains a plurality of halogens.
3. The lithium ion conductor according to claim 1 or 2, wherein The complex halide includes at least one of Br and Cl.
4. The lithium ion conductor according to any one of claims 1 to 3, wherein The complex halide comprises Br and I.
5. A lithium-ion battery comprising a positive electrode, an electrolyte layer and a negative electrode, wherein: At least one of the positive electrode, the electrolyte layer, and the negative electrode includes the lithium ion conductor according to any one of claims 1 to 4.
6. The lithium ion battery according to claim 5, wherein: At least one of the positive electrode, the electrolyte layer, and the negative electrode includes the lithium ion conductor and a sulfide solid electrolyte.
7. A method for producing a lithium ion conductive material, comprising: At least one lithium halide and at least one gallium halide are mixed to obtain a complex halide represented by LiGaX4, wherein X is one or more halogens.
Citation Information
Patent Citations
Negative electrode layer and lithium all-solid battery
JP2020092100A
Solid-state electrolyte layer for all-solid-state lithium-ion secondary battery and all-solid-state lithium-ion secondary battery including the same
JP2020198270A